Increased insulin-like growth factor 1 production by polyploid adipose stem cells promotes growth of breast cancer cells - Fajka-Boja, Roberta; Marton, Annamária; Tóth, Anna; Blazsó, Péter; Tubak, Vilmos; Bálint, Balázs; Nagy, István; Hegedűs, Zoltán; Vizler, Csaba; Katona, Robert L. (BMC cancer, 2018)
Background Adipose-tissue stem cells (ASCs) are subject of intensive research since their successful use in regenerative therapy. The drawback of ASCs is that they may serve as stroma for cancer cells and assist tumor progression. It is disquieting that ASCs frequently undergo genetic and epigenetic changes during their in vitro propagation. In this study, we describe the polyploidization of murine ASCs and the accompanying phenotypical, gene expressional and functional changes under long term culturing. Methods ASCs were isolated from visceral fat of C57BL/6 J mice, and cultured in vitro for prolonged time. The phenotypical changes were followed by microscopy and flow cytometry. Gene expressional changes were determined by differential transcriptome analysis and changes in protein expression were shown by Western blotting. The tumor growth promoting effect of ASCs was examined by co-culturing them with 4 T1 murine breast cancer cells. Results After five passages, the proliferation of ASCs decreases and cells enter a senescence-like state, from which a proportion of cells escape by polyploidization. The resulting ASC line is susceptible to adipogenic, osteogenic and chondrogenic differentiation, and expresses the stem cell markers CD29 and Sca-1 on an upregulated level. Differential transcriptome analysis of ASCs with normal and polyploid karyotype shows altered expression of genes that are involved in regulation of cancer, cellular growth and proliferation. We verified the increased expression of Klf4 and loss of Nestin on protein level. We found that elevated production of insulin-like growth factor 1 by polyploid ASCs rendered them more potent in tumor growth promotion in vitro. Conclusions Our model indicates how ASCs with altered genetic background may support tumor progression.